Human neuroimaging reveals the subcomponents of grasping, reaching and pointing actions. (January 2018) - Cavina-Pratesi, Cristiana; Connolly, Jason D.; Monaco, Simona; Figley, Teresa D.; Milner, A. David; Schenk, Thomas; Culham, Jody C.
Abstract: Although the neural underpinnings of visually guided grasping and reaching have been well delineated within lateral and medial fronto-parietal networks (respectively), the contributions of subcomponents of visuomotor actions have not been explored in detail. Using careful subtraction logic, here we investigated which aspects of grasping, reaching, and pointing movements drive activation across key areas within visuomotor networks implicated in hand actions. For grasping tasks, we find activation differences based on the precision required (fine > coarse grip: anterior intraparietal sulcus, aIPS), the requirement to lift the object (grip + lift > grip: aIPS; dorsal premotor cortex, PMd; and supplementary motor area, SMA), and the number of digits employed (3-/5- vs. 2-digit grasps: ventral premotor cortex, PMv; motor cortex, M1, and somatosensory cortex, S1). For reaching/pointing tasks, we find activation differences based on whether the task required arm transport ((reach-to-point with index finger and reach-to-touch with knuckles) vs. point-without-reach; anterior superior parietal lobule, aSPL) and whether it required pointing to the object centre ((point-without-reach and reach-to-point) vs. reach-to-touch: anterior superior parieto-occipital cortex, aSPOC). For point-without-reach, in which the index finger is oriented towards the object centre but from a distance (point-without-reach > (reach-to-point and reach-to-touch)), we find activation differences that may be related to the communicative nature of the task (temporo-parietal junction, TPJ) and the need to precisely locate the target (lateral occipito-temporal cortex, LOTC). The present findings elucidate the different subcomponents of hand actions and the roles of specific brain regions in their computation.